Comparison of intestinal microbes in female and male Chinese concave‐eared frogs (Odorrana tormota) and effect of nematode infection on gut bacterial communities - Yilin Shu; Pei Hong; Dong Tang; Hui Qing; Oscar Omondi Donde; Huan Wang; Bangding Xiao; Hailong Wu (MicrobiologyOpen, 2019)
Abstract The Chinese concave‐eared frog (Odorrana tormota) is a rare and threatened species with remarkable sexual dimorphism. Intestinal microbes are understood to play important roles in animal physiology, growth, ecology, and evolution. However, little is known about the intestinal microbes in female and male frogs, as well as the contributing effect by gut infesting nematodes to the co‐habiting bacteria and their function in degradation food rich in chitin. Here, this study analyzed the microbiota of the intestinal tract of both female and male, healthy as well as nematode‐infested concave‐eared frogs using high throughput 16S rRNA sequencing and metagenomic techniques. The results showed that the bacterial composition of the microbiota at the phylum level was dominated by Firmicutes, Verrucomicrobia, Bacteroidetes, and Proteobacteria. The study also revealed that the community composition below the class level could be represent sex differences, particularly with regard to Enterobacteriales, Enterobacteriaceae, Peptostreptococcaceae, and Rikenellaceae, among others. Carbohydrate‐active enzyme‐encoding genes and modules were identified in related gut bacteria by metagenomic analysis, with Bacteroidia, Clostridia, and gammaproteobacteria predicted to be the main classes of chitin‐decomposing bacteria in the frog intestine. In addition, the abundance of some bacteria significantly increased or decreased in nematode‐infected hosts compared with healthy individuals, including Verrucomicrobia, Verrucomicrobiae, Negativicutes, Actinobacteria, and Bacilli, among others. This indicates that nematode infection may affect the richness and composition of some gut bacteria.